LANDSCAPE OF VISUAL AI IN INDONESIA'S CREATIVE INDUSTRY: BETWEEN INNOVATION OPPORTUNITIES AND ETHICAL REGULATORY CHALLENGES - Salam, Muhammad Fachrul; Hany Alexandra; Nurul Amalia S; Mohamad Alfauzan Azzubaidi; Dwi Adinda Irfa (Pena Cendekia Insani, 2025)
The rapid development of generative visual AI in Indonesia's digital creative ecosystem has outpaced clear ethical and regulatory frameworks, creating a landscape of opportunities rife with uncertainty. This study maps these complex dynamics using a mixed-methods explanatory sequential design. The quantitative phase involved an online survey of 322 respondents, followed by a qualitative phase through in-depth interviews with 10 selected respondents. The findings indicate a high but pragmatic level of AI adoption (96.6%). There is a strong paradox between enthusiasm for the benefits of AI (Mean > 4.3) and deep concerns about ethical risks (Mean > 4.1), particularly regarding originality. A significant gap was identified between high personal ethical awareness and low understanding of formal regulations (Mean < 3.8). The practical implication of this study is the urgent need to develop ethical guidelines and legal literacy modules for creators in Indonesia.